O apoio matricial em saúde mental no SUS de Belo Horizonte na perspectiva dos trabalhadores - Natália Freitas Dantas (2014)
Support Matrix is a strategy adopted by the Ministry of Health (Brazil 2004a) in order to increase the response capacity of Primary Care and organizing flows, articulate the various levels of care, emphasized the importance of the dialogic process in health work in both individually, and collectively, as well as facilitating the integration of care practices in larger level of activity. Fields and Domitti (2007) conceptualize this new proposal stating that the Matrix Support aims "to provide specialized defense teams and professionals responsible for the care of health problems. (...) Aims to provide both backup care as pedagogical technical support teams to reference. "(P.399-400). Coupled to this, we see the discussion of the Psychiatric Reform bringing the relevance of mental health work in Primary Care, responsible for basic health care, closer to the reality of life for users. In this perspective, the Matrix Support emerges as a proposal for joint care in the primary care mental health, given that the processes of care that you do not walk away from their territory. Given the above, this research therefore has the primary aim of understanding how the matrix support in mental health has been appropriated by psychologists who perform this function with the Primary Health Care experience in the city of Belo Horizonte. The interest in studying psychologists is about the recognized presence of these professionals in the wake of the discussions and debates in the struggles for the transformation of mental health policy. For both, the secondary objectives were: 1) know the history of implementation of mental health and the Mental Health Support Matrix and its linkages with primary care in the health system of Belo Horizonte; 2) know the process of creating teams matricial studied in the context of that city; 3) analyze the perception of psychologists about their role as supporter matrix; 4) describe the practices concerning the work of psychologist supporter. The research was qualitative, using instruments such as semistructured interviews with five individual psychologists involved with the matrix support in mental health and two representatives from the managerial level of the mental health of the municipality of Belo Horizonte network, and participant observation at three meetings matrix support. The analysis of data was collected through content analysis. In the final reflection, one realizes that despite the tensions and challenges, the Matrix Support was perceived as a powerful work of mental health in primary care and has tried to transform the employment relationship in basic health units in the sense of co-responsibility and work integrated between the teams. Nevertheless, it is still necessary to advance as regards the construction of the treatment plan, expanding the scope of interventions beyond the individual clinical care, including the prospect of working with groups and collectives, as well as the perspective of the territory. Moreover, it is also important advance in regard to co-responsibility, the formation of networks, and institutional support.